A new registration method with improved phase congruency for application to GPR images. Issue 7 (3rd July 2022) - Zhang, Pengyu; Shen, Liang; Huang, Xiaotao; Xin, Qin
ABSTRACT: In this letter, we propose an edge detection algorithm and a framework of points matching for ground penetrating radar (GPR) images to achieve the B-Scan image registration of GPR. In our proposed algorithm, the robust edge feature information of GPR images is detected by the improved phase congruency model. Then, the feature points are detected by the GPR image's edge feature in the curvature scale space. Finally, a novel similarity metric is defined for feature point registration. Experimental results show that compared to the classic registration method and the state-of-the-art feature points registration methods, the proposed method shows the best matching performance and robustness in GPR images.